BITs with a bite? EU home investment effects of EU-China bilateral investment treaties - Tero Kuusi; Jyrki Ali-Yrkkö (The Research Institute of the Finnish Economy (ETLA), 2021)
In this paper, we study the impacts of bilateral investment treaties (BITs) between the EU countries and China on EU home investments. We consider BITs as "treatments" that provide further access to global value chains (GVCs). We identify the causal impacts of the BITs on the relationship between home investments and the deepening of GVCs, with identification arising from exogenous, pre-treaty variation in the exposure to the Chinese value chains. We show that strong pre-treaty exposure to the Chinese value chains has led to a further strengthening of the Chinese upstream linkages and a decreasing impact on domestic capital growth in the EU. it seems that the effects of the BITs are strongly felt in growing industries where there have been high capital growth rates, most pronouncedly in the manufacture of computer, electronic, and optical products, and pharmaceuticals. On the other hand, it is also felt in some industries that have had laggard capital growth rates, such as the textile industry. However, it appears that the effect has been heterogeneous, concentrating on countries with low productivity, as relative to the global industry averages. Among the exposed industries with a high pre-treaty fraction of Chinese production, the high-productivity ones tend to increase their relative labor-productivity growth and value-added growth more after the signing of a treaty. The negative link between non-Chinese investments and the pre-treaty exposure also characterizes BITs with China and non-EU countries, but not BITs without China as a partner country.
Keywords: F21; F23; F13; F62; L24; 330; Domestic investments; Foreign investments; Investment treaty; Overseas investments; Global value chain; Bilateral treaties